Pengaruh Pemberian Pupuk Organik Cair Kulit Pisang dan Kotoran Sapi Terhadap Pertumbuhan dan Produksi Tomat (Solanum lycopersicum L.) - Anggreni, Putri Della; Siregar, Maimunah; Lubis, Najla (JURNAL AGROPLASMA, 2025)
Tomato (Solanum lycopersicum L.) is one of the vegetable commodities cultivated by farmers in Indonesia and is considered a multifunctional crop. In addition to being consumed as a vegetable, tomatoes are also used as raw materials in the pharmaceutical and cosmetic industries, as well as in food processing. This research was conducted at the Research Field of Pembangunan Panca Budi University, located in Dusun 3, Sampe Cita Village, Kutalimbaru District, Deli Serdang Regency, North Sumatra, at an altitude of approximately 500 meters above sea level. The aim of the study was to determine the effect of cow manure and banana peel liquid organic fertilizer (POC) on the growth and yield of tomato plants. The experiment employed a factorial randomized block design (RBD) with two factors, namely cow manure (K) and banana peel liquid organic fertilizer (C), each replicated three times. Factor I consisted of cow manure application (K) at four levels: K0 = 0 kg/plot, K1 = 1.5 kg/plot, and K2 = 3 kg/plot. Factor II consisted of banana peel POC application (C) at four levels: C0 = 0 ml/L water/plot, C1 = 175 ml/L water/plot, C2 = 350 ml/L water/plot, and C3 = 525 ml/L water/plot. The results showed that the application of cow manure and the concentration of banana peel POC significantly influenced plant height, stem diameter, number of fruits per plot, fruit weight per sample, total fruit weight per plot, and fruit diameter. However, these treatments did not significantly affect flowering time.. Keywords: cow manure fertilizer, banana peel liquid organic fertilizer (POC), tomato